Development of an interactive digital flipbook for dissertation research dissemination - Marwajih Marwajih; Ghufron, Anik; Siswantoyo Siswantoyo; Ismaniati, Christina; Ramadan, Syahri; Wong Yoke Seng (Jurnal Inovasi Teknologi Pendidikan, 2025)
Doctoral dissertation outputs are often presented in static formats that limit accessibility, thematic exploration, and efficient information retrieval. At the Graduate School of Universitas Negeri Yogyakarta, dissertation mapping (2010–2025) has been disseminated through conventional reports lacking interactivity, thematic search features, and user-friendly navigation, making it difficult for users to explore research trends, methodologies, and findings. To address this limitation, a digital flipbook was developed to provide structured, accessible, and visually engaging access to dissertation data. This study employed a Research and Development (R&D) approach based on the Borg and Gall model, including needs analysis, design planning, prototype development, testing, revisions, large-scale trials, and expert validation. Participants in the needs analysis stage included lecturers and academic staff, while the product evaluation involved doctoral students as primary users. Data were collected through document analysis, interviews, and Likert-scale questionnaires, and analysed using descriptive qualitative and quantitative methods. The large-scale trial with 70 doctoral students yielded a mean score of 4.57 (very feasible) and high reliability (Cronbach’s Alpha = 0.91). Pearson correlation showed a strong relationship between ease of navigation and visual appeal (r = 0.72, p < 0.01), while expert validation indicated high validity (Aiken’s V = 0.88). The findings suggest that the dissertation flipbook is an effective digital dissemination tool that enhances research accessibility, supports thematic exploration, and strengthens research mapping. The flipbook contributes to institutional digital transformation, promotes open access, and supports a data-driven academic culture at the Graduate School of Universitas Negeri Yogyakarta.